Técnicas de geoprocessamento aplicadas aos problemas ambientais que afetam o rio Iaco dentro do limite do município de Sena Madureira-AC - Pereira, Tais Karina Krugerr; Morais, Joselânio Ferreira de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The GIS is an important tool that can be applied in studies of the physical and environmental aspects of the Earth , and in this particular case in watersheds. Advancements in computing added to obtain increasingly immediate results, such as classification algorithms employed here to obtain the product. With it will be possible to analyze and characterize the reality brought by associating with influences exerted by the population on the environment and to warn about the importance of protecting biodiversity for different classes ( settlements , protected areas, private areas and indigenous lands ), surrounding the course of the river, using the techniques of spatial analysis to generate qualitative and quantitative benefits of reality produced by human and natural actions . This work intends to show some conflicts regarding the use and occupation of the next course of IACO river in his portion located in Sena Madureira -AC, which is configured with an essential water course for county areas .